Evidence for persistent multilocus genotypes of Biomphalaria pfeifferi in a natural population in Kenya, with implications for transmission of Schistosoma mansoni - Noel A. Oduor; Daniel W. Kariuki; Gerald M. Mkoji; Polycup O. Oraro; Martina R. Laidemitt; Michelle L. Steinauer; Eric S. Loker; Eric L. Agola (Parasites & Vectors)
Abstract Background Biomphalaria pfeifferi, a predominantly self-fertilizing freshwater snail, is the world’s most important intermediate host for Schistosoma mansoni, one of the causative agents of schistosomiasis, a neglected tropical disease affecting millions of people in sub-Saharan Africa. We sought to determine whether we could identify distinct and persistent lineages of B. pfeifferi within a natural stream habitat in western Kenya, indicative of their asexual descent. We also sought to determine whether infections by S. mansoni or other trematodes were associated with particular lineages. Methodology Utilizing 14 microsatellite markers in a multiplex polymerase chain reaction (PCR) format, we genotyped 502 B. pfeifferi collected in six bimonthly (every other month) sampling times from the same locality in a single habitat (Asao Stream, western Kenya). Snails were isolated and screened for infection with S. mansoni and other trematodes using the shedding method followed by microscopical examination of any cercariae found. Results We identified 26 multilocus genotypes (MLGs), that were present at two or more sampling times. Four MLGs persisted across the entire 10-month sampling period, one of which was represented by 17 individuals. These persistent lineages harbored a variety of trematode species, with S. mansoni being the most common. The persistent MLGs were more likely to have trematode infections than those found only at a single sampling time. Low genetic differentiation was observed between November and March (fixation index among subpopulations [FST] = 0.019; p =  < 0.05). The highest genetic differentiation was observed between July and March (FST = 0.372; p =  < 0.001). Analysis of molecular variance (AMOVA) showed higher variation among individuals within sampling times (58%) than within individuals (33%), and a smaller variation (8%) was found among sampling times. Conclusions By identifying the presence of persistent MLGs and their associations with trematode transmission, this study highlights the importance of considering B. pfeifferi MLGs, some of which could be resistant to infection, when developing strategies to control schistosomiasis transmission within Asao Stream and similar ecosystems across sub-Saharan Africa. Graphical Abstract